Role of mitochondrial dynamics proteins in the pathophysiology of obesity and type 2 diabetes - Zorzano, Antonio; Liesa, Marc; Palacín, Manuel (The international journal of biochemistry & cell biology, 2009)
Mitochondrial dysfunction has been reported in skeletal muscle of obese subjects and of type 2 diabetic patients. Reduced mitochondrial mass and defective activity have been proposed to explain this dysfunction. Alterations in mitochondrial function may be crucial to explain the metabolic changes and insulin resistance that characterize both obesity and type 2 diabetes. Consequently, the identification of the primary mechanisms involved is of great relevance. Mitochondrial dynamics refers to the movement of mitochondria along the cytoskeleton and also to the regulation of mitochondrial morphology and distribution, which depend on fusion and fission events. In recent years, some of the proteins that participate in mitochondrial fusion and fission have been identified in mammalian cells. Recent evidence indicates that proteins participating in these processes are also involved in metabolism. The mitochondrial fusion protein mitofusin 2 stimulates respiration, substrate oxidation and the expression of subunits that participate in respiratory complexes in cultured cells. In this regard, skeletal muscle of obese subjects and of type 2 diabetic patients shows reduced mitofusin 2 expression. Therefore, alterations in the activity of the proteins involved in mitochondrial dynamics, and particularly mitofusin 2, may participate in the reduced mitochondrial function present in skeletal muscle in obesity and in type 2 diabetes.